Implementation of Guidance And Counseling Services in The Field Of Career Development at SMP N 2 Padang - Septiani, Mawar (Lembaga Riset Mutiara Akbar, 2022)
This research is based on the process of implementing guidance and counseling services in the field of career development, because there are still many students who do not understand and do not have career planning. The purpose of this research is to look at the process of implementing guidance and counseling services in the field of career development, identification of 1) Planning for the implementation of counseling services in the field of career development, 2) Implementation of counseling services in the field of career development, and 3) Evaluation of counseling services in the career field. This research uses a qualitative descriptive method. The results of the study reveal that 1) the planning for the implementation of guidance and counseling services in the field of development can be seen from the results of the analysis of students, the needs of students at that time and the 2013 guide curriculum, 2) Implementation of counseling services in the field of career development through classical services, individual counseling and tests. talent interests, 3) Evaluation of counseling services in the field of career development is carried out after the services are provided in the form of questions and statements of students in accordance with the 2013 curriculum format. offers guidance and counseling services on career development..